The social factors related to girls’ attitude towards conspicuous consumption - Field study on Qassim University students – Saudi Arabia – - Al-Suhaibani, Fatimah Abdullah (Journal of Humanities & Social Sciences, 2020)
The aim of this research is to identify some of the social factors related to the girls ’attitude towards conspicuous consumption. These factors represent the place of residence, the prevailing pattern of consumption among family members, the educational level of the parents and the occupation of parents. This research relied on the social survey method and questionnaire as a tool to collect data. The sample consisted of 216 Qassim University female students from various disciplines.The research reached several results, namely: that the trend of the sample towards conspicuous consumption is "weak", in addition to the absence of a relationship between the trend towards conspicuous consumption and each of the (place of residence, the prevailing pattern of consumption among family members, the educational level of parents, the occupation of parents) factors. The research highlights the importance of maintaining a low trend towards conspicuous consumption by spreading awareness by educational institutions, media and others, in addition to conducting more extensive studies on " conspicuous consumption" to cover the problem in all its aspects.
Keywords: social factors; attitude; ostentatious consumption